Ceramic Sensors: A mini-review of their applications - Krishna Prasad, N. V.; Venkata Prasad, K.; Ramesh, S.; Phanidhar, S. V.; Venkata Ratnam, K.; Janardhan, S.; Manjunatha, H.; Sarma, M. S. S. R. K. N.; Srinivas, K. (Frontiers in Materials, 2020)
Ceramics are solid materials that comprise inorganic compounds of metal or metalloids and non-metals with covalent or ionic bonds. Commonly known ceramics are brick, porcelain and earthenware. Substances with special properties make advanced ceramics,also called fine, engineering, high performance, high tech or technical ceramics. Traditionally ceramics are made of powder and then fabricated into material by applying heat which exhibit strength, hardness, brittleness and low electrical conductivity. Ceramics can be widely used almost in every application that includes the field of engineering, industry, medical, automotive, space and environment. One of the most important applications of ceramics is to use as sensor in many areas. Traditional ceramics can be used in sensors where durability and toughness is a prerequisite while advanced ceramics can be used where more emphasis is laid towards improved requirement of electrical, thermal, magnetic and optical properties. Ceramics used in sensors require long durable life, high tolerance of temperature, robust nature, should be able to undergo direct contact with liquid media. Ceramics are extensively used as temperature, humidity, pressure, oxygen, proximity, automobile, capacitive, oil level and corrosion sensors (Liam Critchley, 2020). Mengying Xie et.al., 2018 demonstrated flexible and active shear and pressure sensors using lead zirconate titanate that measure strain ,acceleration and touch sensors that detects longitudinal, transverse and shear loads. This review paper precisely reports ceramic sensors and their applications in household, industrial, medical, automotive and environmental applications with more emphasis on environmental sensors.